Meta-analysis of segmentectomy versus lobectomy for radiologically pure solid or solid-dominant stage IA non-small cell lung cancer - Rao, Sunyin (J Cardiothorac Surg, 2019)
OBJECTIVE: Whether segmentectomy can be used to treat radiologically determined pure solid or solid-dominant lung cancer remains controversial owing to the invasive pathologic characteristics of these tumors despite their small size. This meta-analysis compared the oncologic outcomes after lobectomy and segmentectomy regarding relapse-free survival (RFS) and overall survival (OS) in patients with radiologically determined pure solid or solid-dominant clinical stage IA non-small cell lung cancer (NSCLC). METHODS: A literature search was performed in the MEDLINE, EMBASE, and Cochrane Central databases for information from the date of database inception to March 2019. Studies were selected according to predefined eligibility criteria. The hazard ratio (HR) and associated 95% confidence interval (CI) were extracted or calculated as the outcome measure for data combining. RESULTS: Seven eligible studies published between 2014 and 2018 enrolling 1428 patients were included in the current meta-analysis. Compared with lobectomy, segmentectomy had a significant benefit on the RFS of radiologically determined pure solid or solid-dominant clinical stage IA NSCLC patients (combined HR: 1.46; 95% CI, 1.05–2.03; P = 0.024) and there were no significant differences on the OS of these patients (HR: 1.52; 95% CI, 0.95–2.43; P = 0.08). CONCLUSIONS: Segmentectomy leads to lower survival than lobectomy for clinical stage IA NSCLC patients with radiologically determined pure solid or solid-dominant tumors. Moreover, applying lobectomy to clinical stage IA NSCLC patients with radiologically determined pure solid or solid-dominant tumors (≤2 cm) could lead to an even bigger survival advantage. However, there are some limitations in the present study, and more evidence is needed to support the conclusion.